1996
DOI: 10.1038/ng0496-427
|View full text |Cite
|
Sign up to set email alerts
|

A locus for bipolar affective disorder on chromosome 4p

Abstract: The main clinical feature of bipolar affective disorder is a change of mood to depression or elation. Unipolar disorder, also termed major depressive disorder, describes the occurrence of depression alone without episodes of elevated mood. Little is understood about the underlying causes of these common and severe illnesses which have estimated lifetime prevalences in the region of 0.8% for bipolar and 6% for unipolar disorder. Strong support for a genetic aetiology is found in the familial nature of the condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
207
1
6

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(220 citation statements)
references
References 27 publications
6
207
1
6
Order By: Relevance
“…38 Usher syndrome can cause central nervous system structural changes 39 and psychosis, 40 and there is one report of increased incidence of bipolar disorder among adults with prelingual-onset nonsyndromic deafness, 41 but it is not known if any of those patients carried the 'whirler' mutation. Finally, SORCS2 maps to a region on chromosome 4p that has been widely linked to bipolar disorder 42 (Supplementary References). SORCS2 encodes a VPS10 domain-containing receptor prominently expressed in the developing brain.…”
Section: Ae Baum Et Almentioning
confidence: 99%
“…38 Usher syndrome can cause central nervous system structural changes 39 and psychosis, 40 and there is one report of increased incidence of bipolar disorder among adults with prelingual-onset nonsyndromic deafness, 41 but it is not known if any of those patients carried the 'whirler' mutation. Finally, SORCS2 maps to a region on chromosome 4p that has been widely linked to bipolar disorder 42 (Supplementary References). SORCS2 encodes a VPS10 domain-containing receptor prominently expressed in the developing brain.…”
Section: Ae Baum Et Almentioning
confidence: 99%
“…Among these regions we retained the 4p16 locus since significant linkage with BD was found in Scottish, Danish and American pedigrees. [2][3][4][5] A recent study on Faroese population confirmed the link between this locus and BD and schizophrenia. 6 The 4p16 region encodes several interesting candidate genes such as ADRA2C (a-adrenergic receptor 2C), WFS1 (wolframin; heterozygous carriers display an estimated 26-fold increased incidence of psychiatric illness 7 ) or DRD5 (dopamine D5 receptor) genes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, findings in 4p, 4q, 8q, 10p, 12q24, 13q, 18p, 18q, 21q, and 22q have been supported by more than one study. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] However, these studies have not identified any specific genes, and a recent metaanalysis of available genome scans showed no regions with a conclusive evidence of linkage. 20 The relatively slow progress of gene-mapping efforts is often explained by the 'complex' nature of the illness and of the genotype-phenotype relation.…”
mentioning
confidence: 99%